Effects of protein supplementation frequency on physiological responses associated with reproduction in beef cows - Cappellozza, B. I.; Cooke, R. F.; Reis, M. M.; Marques, R. S.; Guarnieri Filho, T. A. [UNESP]; Perry, G. A.; Jump, D. B.; Lytle, K. A.; Bohnert, D. W. (Amer Soc Animal Science, 2015)
The objective of this experiment was to determine if frequency of protein supplementation impacts physiological responses associated with reproduction in beef cows. Fourteen nonpregnant, nonlactating beef cows were ranked by age and BW and allocated to 3 groups. Groups were assigned to a 3 x 3 Latin square design, containing 3 periods of 21 d and the following treatments: 1) soybean meal supplementation daily (D), 2) soybean meal supplementation 3 times/week (3WK), and 3) soybean meal supplementation once/week (1WK). Within each period, cows were assigned to an estrus synchronization protocol: 100 mu g of GnRH + controlled internal drug release device (CIDR) containing 1.38 g of progesterone (P-4) on d 1, 25 mg of PGF(2 alpha) on d 8, and CIDR removal + 100 mu g of GnRH on d 11. Grass-seed straw was offered for ad libitum consumption. Soybean meal was individually supplemented at a daily rate of 1 kg/cow (as-fed basis). Moreover, 3WK was supplemented on d 0, 2, 4, 7, 9, 11, 14, 16, and 18 whereas 1WK was supplemented on d 4, 11, and 18. Blood samples were collected from 0 (before) to 72 h after supplementation on d 11 and 18 and analyzed for plasma urea-N (PUN). Samples collected from 0 to 12 h were also analyzed for plasma glucose, insulin, and P-4 (d 18 only). Uterine flushing fluid was collected concurrently with blood sampling at 28 h for pH evaluation. Liver biopsies were performed concurrently with blood sampling at 0, 4, and 28 h and analyzed for mRNA expression of carbamoyl phosphate synthetase I (CPS-I; h 28) and CYP2C19 and CYP3A4 (h 0 and 4 on d 18). Plasma urea-N concentrations were greater (P < 0.01) for 1WK vs. 3WK from 20 to 72 h and greater (P < 0.01) for 1WK vs. D from 16 to 48 h and at 72 h after supplementation (treatment x hour interaction, P < 0.01). Moreover, PUN concentrations peaked at 28 h after supplementation for 3WK and 1WK (P < 0.01) and were greater (P < 0.01) at this time for 1WK vs. 3WK and D and for 3WK vs. D. Expression of CPS-I was greater (P < 0.01) for 1WK vs. D and 3WK. Uterine flushing pH tended (P <= 0.10) to be greater for 1WK vs. 3WK and D. No treatment effects were detected (P >= 0.15) on expression of CYP2C19 and CYP3A4, plasma glucose, and P-4 concentrations, whereas plasma insulin concentrations were greater (P <= 0.03) in D and 3WK vs. 1WK. Hence, decreasing frequency of protein supplementation did not reduce uterine flushing pH or plasma P-4 concentrations, which are known to impact reproduction in beef cows.
Keywords: beef cows; plasma urea-N; progesterone; protein; supplementation frequency; uterine pH